IMPLEMENTASI KEBIJAKAN PENETAPAN INPASSING JABATAN FUNGSIONAL GURU BUKAN PNS DAN ANGKA KREDITNYA DI SD SWASTA KOTA SEMARANG - Nurwinda Nugraheni; Ari Subowo; Aufarul Marom (Journal of Public Policy and Management Review, 2013)
Improving the quality of teachers is the one of government's implementation inpassing policy and credit points appliance for non Governmental teachers. It’s based on regulation of national education minister No. 47 in 2005 and later revised to No. 22 in 2010. This research aims to provide an explanation of the policy implementation inpassing GBPNS happened in Semarang in particular private elementary school and the factors affect on that. It’s used used a qualitative descriptive method by analyzing the implementation of the policy inpassing GBPNS. These research uses the theory of George Edward III to analyze the factors that influence policy implementation. The results of this research showed that a lack of awareness of private schools for educational programs so there are many private teachers in particular Permanent Teachers Foundation (GTY) inpassed yet. In this policy the requirements and procedures of inpassing and implementation is not optimal. Another factor that caused the school administration hasn’t managed properly. Some suggestions for policy implementation of inpassing GBPNS can be better, with better motivation and further improvement on the performance of the Department of Education. Beside that private schools has to be more concerned on the education programs.